Analisis Komoditas Sayuran Unggulan Kabupaten Minahasa Selatan - Palungan, Natalia; Lolowang, Tommy Fredy; Tambas, Jane Sulinda (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2025)
This study aims to (1) describe the harvest area, production, and productivity of vegetable commodities in South Minahasa Regency and (2) identify vegetable commodities that have competitive advantages in the region. Secondary data on harvest areas and vegetable production for the 2019-2023 period from South Minahasa Regency and North Sulawesi were analyzed using the Location Quotient (LQ) method with a combined approach of Static Location Quotient (SLQ) and Dynamic Location Quotient (DLQ). The results showed that (1) the harvest areas of leeks and potatoes increased, while garlic experienced a significant decline until it was not cultivated in 2022-2023. Chili and long beans have the highest average productivity, followed by chayote and cucumber. (2) LQ-DLQ analysis classifies vegetable commodities into four categories: superior (leeks, potatoes, cabbage, petsai; 23%), mainstay (shallots, beans, large chili, cayenne pepper, long beans, water spinach, cucumber, tomatoes, chayote, eggplant, carrots; 65%), lagging (garlic, spinach; 12%), and no prospective commodities were found.